Juridical Analysis of the Use of Private Deeds as a Basis for Making Authentic Deeds by Notaries in the Conception of Legal Certainty - Tobi, Andri (Jurnal Konstatering, 2022)
This study aims to determine and analyze in a juridical way the use of private deed as the basis for making authentic deed by a Notary in the conception of legal certainty. This study uses a sociological juridical approach with descriptive analytical research specifications. The type of data used is primary data, namely the results of interviews and secondary data in the form of legislation, jurisprudence, court decisions that have permanent legal force, books, journals as well as expert opinions and other legal materials. Research data was collected through interviews and literature study. The data analysis method in this study uses qualitative data analysis methods. The research results show that: First, the use of an underhanded deed in making an authentic deed by a Notary is contrary to the elements of an authentic deed which require and determine that an authentic deed must be sufficient and perfect evidence regarding everything described in it which binds the parties and their heirs and those who obtain the rights thereof, as well as in the event that proving an authentic deed is sufficient evidence that does not require additional evidence, this is different from an private deed whose strength of proof depends on whether or not the deed under the hand is acknowledged by the maker, denial of the deed under the hand will place the burden of proof on the party using the deed under the hand. Second, from the aspect of authority,Keywords: Authentic; Construction; Private.